العلاقات المائية التركية- العراقية بين الصراع والتعاون Turkish-Iraqi water relations between conflict and cooperation - لعجال, ليلى; ازروال, يوسف (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2022)
تهدف الدراسة إلى عرض وتحليل لموضوع العلاقات المائية التركية العراقية، نظرا لما تتمتع به الموارد المائية من دور في ضمان الاستقرار في العلاقات الدولية، إذا استندت على إطار تعاوني دولي، بالمقابل يمكن أن تؤدي إلى تأسيس صراع دائم بين الدول إذا ارتكز كل طرف على مصالحه القومية فحسب. لذلك سنحاول عبر هذه الورقة أن نركز على دراسة المسألة المائية في العلاقات المائية بين تركيا والعراق، خاصة مع استمرار تركيا في تجسيد مشاريعها المائية على نهري دجلة والفرات، وبالتالي استمرار المعضلة المائية كمتغير مؤثر في العلاقات المائية بين العراق وتركيا. Abstract: The study aims to present and analyze the issue of Turkish-Iraqi water relations, because the importance of water resources in achieving stability in (ir), if it is based on international cooperation framework, Conversely, it can be create a permanent conflict between states if each party is based on its national interests only. Therefore, we will try through this paper to study the water issue in the water relations between Turkey and Iraq, especially with Turkey continuing to embody its water projects on the Tigris and Euphrates rivers, the continuation of the water dilemma as an influential variable in the water relations between Iraq and Turkey.